Fighting With Siblings and With Peers Among Urban High School Students. (August 2015) - Johnson, Renee M.; Duncan, Dustin T.; Rothman, Emily F.; Gilreath, Tamika D.; Hemenway, David; Molnar, Beth E.; Azrael, Deborah
Understanding the determinants of fighting is important for prevention efforts. Unfortunately, there is little research on how sibling fighting is related to peer fighting. Therefore, the aim of this study was to evaluate the association between sibling fighting and peer fighting. Data are from the Boston Youth Survey 2008, a school-based sample of youth in Boston, MA. To estimate the association between sibling fighting and peer fighting, we ran four multivariate regression models and estimated adjusted prevalence ratios and 95% confidence intervals. We fit generalized estimating equation models to account for the fact that students were clustered within schools. Controlling for school clustering, race/ethnicity, sex, school failure, substance use, and caregiver aggression, youth who fought with siblings were 2.49 times more likely to have reported fighting with peers. To the extent that we can confirm that sibling violence is associated with aggressive behavior, we should incorporate it into violence prevention programming.